Emerging respiratory viruses - discoveries between 2001 and 2005 - Fouchier, Ron (Henry Stewart Talks, 2007)
Respiratory viruses, Respiratory disease, Virus discovery, Koch's postulates, Human metapneumovirus, Human coronavirus NL63, Human coronavirus HKU, Human bocavirus
Reviewed at 2017/05/02